Association between the serotonin transporter promoter polymorphism and personality traits in a primarily female population sample - Benjamin D. Greenberg; Qian Li; Frank R. Lucas; Stella Hu; Leo A. Sirota; Jonathan Benjamin; Klaus‐Peter Lesch; Dean H. Hamer; Dennis L. Murphy (2000)
The serotonin transporter (5-HTT) regulates serotonergic neurotransmission and is thought to influence emotion. A 5-HTT-linked polymorphic region (5-HTTLPR) has two common variants, short (s) and long (l). We previously found population and within-family associations between the lower-expressing s allele and neuroticism, a trait related to anxiety, hostility, and depression, on a standard measure (the NEO Personality Inventory, Revised [NEO-PI-R]) in a primarily male population (n=505), and that the s allele was dominant. We investigated this association in a new sample (n=397, 84% female, primarily sib-pairs). The results robustly replicated the 5-HTTLPR neuroticism association, and the dominance of the s allele. Combined data from the two studies (n=902) showed a highly significant association between the s allele and higher NEO Neuroticism both across individuals and within families. Association between genotype and a related measure, Anxiety on the 16PF inventory, was replicated in the new population and within families in the combined sample. Association to another trait, estimated TPQ Harm Avoidance, was not replicated in the new sample but found only within the combined sibship group. Another association found in our original study, between the s allele and lower scores on NEO-PI-R Agreeableness, was also replicated and was more robust in the current and the combined samples. Associations between the functional 5-HTTLPR polymorphism were similar in women and men. These results help to define specific personality features reproducibly associated with 5-HTTLPR genotype. Such associations were strongest for traits defined by the NEO, enhancing the attractiveness of the five-factor personality model in genetic research on complex behavioral dimensions. Am. J. Med. Genet. (Neuropsychiatr. Genet.) 96:202–216, 2000. Published 2000 Wiley-Liss, Inc.